PERANCANGAN SISTEM PENGUKUR PH AIR SUMUR MASYARAKAT KELURAHAN TANJUNG SENGKUANG KOTA BATAM MENGGUNAKAN ARDUINO UNO - Febrianto, Rizki Amin; Hotma Pangaribuan (Computer Science and Industrial Engineering, 2024)
The growth of technology and industry is growing rapidly in several Indonesian provinces, especially in Tanjung Sengkuang urban village of Batam City, where many factories are established around residential areas. Well water is the main source of water for the local community. However, the quality of the well water has not been accurately measured so that people do not know whether the water is safe to use. The designed water pH measuring system consists of a pH sensor as input, then the measurement results from the sensor will be sent through Arduino Uno to be displayed on the LCD, on the other hand, Arduino Uno also sends data from the measurement results to NodeMCU to be sent to the database, after which users can see the results of the water pH measurement through smart devices, anywhere and anytime. It is hoped that with this well water pH measuring system, people can monitor the quality of well water used and can immediately take appropriate action if problems are found in the quality of the water.